A typical method for decellularization of plants as biomaterials - Melis Toker-Bayraktar; Melek İpek Ertugrul; Sedat Odabas; Bora Garipcan (MethodsX, 2023)
Decellularization is a process by which cells are removed from tissues or organs, leaving behind the extracellular matrix (ECM) structure. This process has gained interest in the fields of tissue engineering and regenerative medicine as a way to prepare suitable scaffolds for tissue reconstruction. Although the initial efforts come with the animal tissues, this technique can also be applied to various plant tissues with simple modifications, as plant-derived biomaterials have the benefit of being biocompatible and serving as a safe, all-natural substitute for synthetic or animal originated materials. Additionally, plant-derived biomaterials may help cells grow and differentiate, creating a three-dimensional environment for tissue regeneration and repair. Here we demonstrate a general method for plant tissue decellularization, including already experienced approaches and techniques. • Exhibit the basic steps for plant decellularization, which may be applied to several other plant tissues. • The proposed approach may be optimized considering various intended uses. • Gives basic information for the determination of decellularization efficiency.